Euphorstranoids A and B, two highly rearranged ingenane diterpenoids from Euphorbia stracheyi: structural elucidation, chemical transformation, and lipid-lowering activity. Issue 3 (24th December 2021) - Yuan, Fang-Yu; Pan, Yue-Hua; Yin, Ai-Ping; Li, Wei; Huang, Dong; Yan, Xue-Long; Wu, Shu-Qi; Tang, Gui-Hua; Pu, Rong; Yin, Sheng
Abstract : Euphorstranoids A (1 ) and B (2 ), two highly rearranged ingenane diterpenoids with an unusual 5/6/7/3 carbon ring system, were isolated from Euphorbia stracheyi . Abstract : Euphorstranoids A (1 ) and B (2 ), two highly rearranged ingenane diterpenoids with an unusual 5/6/7/3 carbon ring system, were isolated from Euphorbia stracheyi . Their structures were determined by a combination of spectral, chemical, and X-ray diffraction methods. The plausible biosynthetic pathway of 1 and 2 was proposed and chemically mimicked. Compounds 1 and 2 significantly inhibited the triglyceride (TG) level in 3T3-L1 adipocytes via retarding cell adipogenesis at the early stage.